SIMULASI SISTEM KENDALI DAYA REAKTIF TIGA FASE MENGGUNAKAN KAPASITOR VARIABEL (MERS) YANG TERINTEGRASI PARALEL DENGAN GENERATOR SINKRON DAN GENERATOR INDUKSI - PUTRA, YUDI UTOMO; Wijaya, F. Danang ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Now, distributed generating or DG becomes an interesting research object to be investigated. DG is one way to increase the power capacity due to shortage of power in the electrical system. Induction machine is attractive for generation in DG. Induction machine is simple machines in operation, low cost and rugged. In order to generate voltage, induction machine absorbs reactive power from outside. To fullfil the reactive power in isolated operation, induction machine required reactive power from capacitor. But with the change of load, there will be a change in the reactive power demand. So it needed a tool that can control the amount of reactive power that can be generated. One of the tools that can control reactive power is SVC MERS (Static VAR Compensator Magnetic Energy Recovery Switch). This research investigated reactive power control which required by 1500W, 380 volt line to line induction generator in paralel with 3000 W, 380 volt line to line syncrhonous generator to supply the simulation is done by PSIM. SVC MERS can control loads reactive power to achieve constant voltage of system. SVC MERS injected about 1206,5 VAR in no load to 1519,4 VAR in full load.